A Study of the Ellipsoid Algorithm - Montoro Alegre, Edinson (2018)
In the present work are presented the principal lemmas and theorems that are based and prove the benefits of the Khachiyan ellipsoid algorithm, but in a less complicated way than the original work in order to make available to the interested parties and the students of the area of optimization a subject so important from the theoretical point of view and that has been the starting point of many other research work.